Pengaruh Jenis dan Kerapatan Gulma terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L.) - Alvionita, Chintya Ayu; Hamim, Herawati; Sembodo, Dad R. J. (Jurnal Penelitian Pertanian Terapan, 2016)
Maize production in each year tends to decrease. One reason is the weeds. Weeds is animportant issue because it can compete with the main crop that can reduce crop production.The purpose of this research to determine: (1). The effect of weeds species on the growth andproduction of maize, (2). The effect of weed density on the growth and production of maize,(3). Interaction between the type and density of weeds in influencing the growth andproduction of maize. The research was conducted in Natar, South Lampung and WeedLaboratory Faculty of Agriculture, university of Lampung from December 2014 to April2015. The treatments arranged factorial (3x5) in a strip plot design with three replications.The first factor is the species of weed that are Asystasia gangetica, Rottboelia exaltata, andCyperus rotundus. The second factor is 5 weed density that are 0, 10, 20, 40, and 80populations of weeds/m2. If the assumptions are met, the data is analyzed using ANOVA,followed by Least Significant Difference Test (LSD) 5%. The result showed that : (1).Species of weeds affects plant shoot dry weight, the weight of maize cobs, and the weight ofgrain maize but did not affect plant height, number of leaves, plant populations, cob length,cob diameter, and weighs 100 grains. (2). The density of 40 weeds/m2affects weight of 100grains, but the density of 10, 20, and 80 weeds/m2did not affect the growth and productionof maize. (3). There is no interaction between species and density of weeds in influencingthe growth and production of maize.Keyword: maize, weeds, competition